2019
DOI: 10.3171/2018.1.jns172733
|View full text |Cite
|
Sign up to set email alerts
|

A football helmet prototype that reduces linear and rotational acceleration with the addition of an outer shell

Abstract: OBJECTIVE Amid the public health controversy surrounding American football, a helmet that can reduce linear and rotational acceleration has the potential to decrease forces transmitted to the brain. The authors hypothesized that a football helmet with an outer shell would reduce both linear and rotational acceleration. The authors' objectives were to 1) determine an optimal material for a shock-absorbing outer shell and 2) examine the ability of an outer shell to reduce linear and/or rotational acceleration. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Specifically, Breedlove and colleagues evaluated the Guardian Cap and demonstrated that the device reduced force at velocities high enough to cause skull fracture, but failed to mitigate impact forces at the low and medium velocities typically involved in concussion [110]. One study designed a helmet prototype that significantly reduced rotational acceleration with the addition of an outer shell [111], suggesting a potential promising direction for future helmet design. Further study is necessary to evaluate how implementation of various designs may affect the incidence of concussion during real-time play.…”
Section: Future Directionsmentioning
confidence: 99%
“…Specifically, Breedlove and colleagues evaluated the Guardian Cap and demonstrated that the device reduced force at velocities high enough to cause skull fracture, but failed to mitigate impact forces at the low and medium velocities typically involved in concussion [110]. One study designed a helmet prototype that significantly reduced rotational acceleration with the addition of an outer shell [111], suggesting a potential promising direction for future helmet design. Further study is necessary to evaluate how implementation of various designs may affect the incidence of concussion during real-time play.…”
Section: Future Directionsmentioning
confidence: 99%
“…NOCSAE testing methods only require tolerances on helmet performance based on linear accelerations (Levy et al, 2004;Lloyd & Conidi, 2016). While this may be impactful for catastrophic injuries, as some speculate are influenced greater by linear acceleration and high velocities (Broglio et al, 2012), many studies have reflected the even greater influence of rotational accelerations on injury risk, especially in cases of mTBI (Ford et al, 2018;Hernandez, Shull, & Camarillo, 2015;Levy et al, 2004;Lloyd & Conidi, 2016;Merchant-Borna et al, 2016;Zuckerman et al, 2019). Yet, many still support the hypothesis that rotational accelerations provide a superior indication of concussion risk as well as catastrophic injury risk (Levy et al, 2004;Lloyd & Conidi, 2016).…”
Section: Human Studies and Kinematic Measurementsmentioning
confidence: 99%
“…While many researchers have focused on comparing current helmets designs to one another and subjecting them to newer testing procedures in hopes of altering NOCSAE standards; other research groups have started developing helmet designs that can better attenuate impact forces, so the head undergoes less linear and rotational movement. These researchers have highlighted the potential use of exterior padding or shells for greater attenuation with optimistic results (Nakatsuka & Yamamoto, 2014;Zuckerman et al, 2019). However, the skull and brain move very differently relative to one another.…”
Section: Football Helmet Optimizationmentioning
confidence: 99%
“…60 • Improved protective equipment, particularly new helmet designs that might reduce the deceleration the brain undergoes following an impact. 61 • Development of reliable sensors that could measure the relevant forces each player's head area is exposed to, so that if a biologically relevant index of risky exposure could be developed, employers would be able to gauge whether each player was approaching an unacceptable amount of exposure and needed to have time to "recover" before additional exposure. h • Development of devices that might reduce individual susceptibility to the consequences of RHI.…”
Section: From Analysis To Actionmentioning
confidence: 99%